2016
DOI: 10.3109/09273948.2016.1160130
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Dexamethasone Implant for the Treatment of Macular Edema in Chronic Non-infectious Uveitis

Abstract: The DEX implant is an effective adjunct treatment to systemic corticosteroid or immunomodulatory therapy. Additional research is required to determine the efficacy of DEX implant as monotherapy for controlling chronic uveitic macular edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 14 publications
1
21
1
Order By: Relevance
“…18 Another study reported that the improvements in BCVA and central retinal thickness at 1 month were similar (not significantly different) following the first and second implants. 84 In a study of uveitis patients the median time from first to second implant was 10 months 50 whereas in four studies of uveitic macular oedema the mean/median time from first to second implant was 4.7, 81 5.0, 51 7.1 83 and 10 86 months. The mean time from second to third implant was 3.4 months in one study of uveitic macular oedema.…”
Section: Dexamethasone Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Another study reported that the improvements in BCVA and central retinal thickness at 1 month were similar (not significantly different) following the first and second implants. 84 In a study of uveitis patients the median time from first to second implant was 10 months 50 whereas in four studies of uveitic macular oedema the mean/median time from first to second implant was 4.7, 81 5.0, 51 7.1 83 and 10 86 months. The mean time from second to third implant was 3.4 months in one study of uveitic macular oedema.…”
Section: Dexamethasone Studiesmentioning
confidence: 99%
“…18,50,51,[79][80][81][82][83][84][85][86] This is based on data from the company submission for DEX; 43 the original study publications have not been examined because of time constraints. These data are included here as they provide some data on repeat implants, implants in both eyes and corticosteroid reduction, which were not assessed in the HURON trial.…”
Section: Dexamethasone Studiesmentioning
confidence: 99%
“…Intravitreal drugs are now considered as a safe and effective treatment option for the management of noninfectious uveitis, especially in patients with unilateral disease without any systemic component. [ 15 16 ] This article reviews the various intravitreal drugs used for the treatment of ME secondary to noninfectious uveitis.…”
mentioning
confidence: 99%
“…Topical DEX has proven efficacious in the management of postoperative inflammation in the anterior segment after cataract surgery, treatment of anterior uveitis (iritis) and dry-eye disease symptoms [3][4][5]. Intravitreal administration of DEX has been effective in the treatment of macular edema following retinal vein occlusion, diabetic macular edema [6][7][8], and non-infectious uveitis [9], particularly when other therapeutic agents have failed to provide treatment benefits. However, DEX has a short halflife [10], and requires multiple applications.…”
mentioning
confidence: 99%